Peran Dan Pengaruh Fintech Dalam Meningkatkan Literasi Keuangan Dan Mendukung Proses Bisnis Sebagai Upaya Keberlangsungan Bisnis UMKM Di Kota Boyolali Dengan Pendekatan Mixed Method - Pratiwi, Yunita Niqrisah Dwi; Theorupun, Milka Susana; Setiawati, Donna (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Analyzing the role and impact of fintech in improving financial literacy and supporting MSME business activities in Boyolali City is the purpose of this study. A mixed method approach was used in this study, namely combining quantitative data through surveys of MSME actors and qualitative data through in-depth interviews with relevant stakeholders. The results of the study indicate that the application of financial technology (fintech) significantly increases MSME actors' access and understanding of financial products and services. In addition, fintech functions to simplify business processes, improve operational efficiency, and expand market coverage. Thus, this study emphasizes the importance of supporting fintech adoption as a strategy to improve financial literacy and the sustainability of MSME businesses in Boyolali. Recommendations are given to policy makers and fintech service providers to develop more integrated programs to empower MSMEs sustainably